A Comment on "Muscle Xenografts Reproduce Key Molecular Features of Facioscapulohumeral Muscular Dystrophy": What Is New and What Has Already been Done and Reported but Was Not Quoted?. (20th July 2020) - Skuk, Daniel; Tremblay, Jacques P
A study was recently published that sought to develop an in vivo model of facioscapulohumeral muscular dystrophy by transplanting muscle precursor cells from a patient into immunodeficient mice. The study largely applied the methodology used by our team in a study published more than two decades ago with a similar objective, albeit for another muscular dystrophy. However, our study is not cited, leaving the wrong idea that the concept, methodology, and part of the results are original to this recent study. Although the recent study is of interest, the omission of our publication, as well as other relevant references, deprives it of an adequate scientific context. We, therefore, want to point out the importance of a careful bibliographic search in any scientific work.